An update on the pharmaceutical management of thrombosis. (1st November 2016) - Cosmi, Benilde
ABSTRACT: Introduction: Anticoagulants such as heparins and vitamin K antagonists (VKA) are effective for thrombosis prevention and treatment, but are associated with the risk of bleeding and other limitations, spurring the search for improved drugs. Areas covered: to evaluate the newer anticoagulants, focusing on those tested in phase III clinical trials such as direct oral anticoagulants (DOACs), antisense oligonucleotides (ASO) and warfarin analogues. DOACs such as dabigatran, rivaroxaban, apixaban and edoxaban are licensed for stroke prevention in atrial fibrillation and treatment of venous thromboembolism, dabigatran, rivaroxaban and apixaban for postoperative thromboprophylaxis in patients undergoing elective hip or knee arthroplasty and rivaroxaban for secondary prevention of acute coronary syndromes. ASO interfering with Factor XI hepatic synthesis were effective and safe for thromboprophylaxis in elective knee arthroplasty. Expert opinion: DOACs have overcome some limitations of anticoagulants such as VKA, but are still associated with a risk of bleeding and they lack both standardized and widely available tests measuring their anticoagulant effect and a reversal agent, except for idarucizumab, specific for dabigatran, in case of major or life threatening bleeding or emergency surgery. Agents targeting Factor XI and possibly Factor XII may be ideal anticoagulants, as they can prevent thrombosis with low bleeding risk.